Inhibiting Drivers of Non-mutational Drug Tolerance Is a Salvage Strategy for Targeted Melanoma Therapy - Smith, Michael P; Brunton, Holly; Rowling, Emily J; Ferguson, Jennifer; Arozarena, Imanol; Miskolczi, Zsofia; Lee, Jessica L; Girotti, Maria R; Marais, Richard; Levesque, Mitchell P; Dummer, Reinhard; Frederick, Dennie T; et al. (Cancer cell, 2016)
Once melanomas have progressed with acquired resistance to mitogen-activated protein kinase (MAPK)-targeted therapy, mutational heterogeneity presents a major challenge. We therefore examined the therapy phase before acquired resistance had developed and discovered the melanoma survival oncogene MITF as a driver of an early non-mutational and reversible drug-tolerance state, which is induced by PAX3-mediated upregulation of MITF. A drug-repositioning screen identified the HIV1-protease inhibitor nelfinavir as potent suppressor of PAX3 and MITF expression. Nelfinavir profoundly sensitizes BRAF and NRAS mutant melanoma cells to MAPK-pathway inhibitors. Moreover, nelfinavir is effective in BRAF and NRAS mutant melanoma cells isolated from patients progressed on MAPK inhibitor (MAPKi) therapy and in BRAF/NRAS/PTEN mutant tumors. We demonstrate that inhibiting a driver of MAPKi-induced drug tolerance could improve current approaches of targeted melanoma therapy.